If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = (3x + -2) Reorder the terms: 7 = (-2 + 3x) Remove parenthesis around (-2 + 3x) 7 = -2 + 3x Solving 7 = -2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 7 + -3x = -2 + 3x + -3x Combine like terms: 3x + -3x = 0 7 + -3x = -2 + 0 7 + -3x = -2 Add '-7' to each side of the equation. 7 + -7 + -3x = -2 + -7 Combine like terms: 7 + -7 = 0 0 + -3x = -2 + -7 -3x = -2 + -7 Combine like terms: -2 + -7 = -9 -3x = -9 Divide each side by '-3'. x = 3 Simplifying x = 3
| 6(x+8)-3=39 | | -10x+3=103 | | .05*x=10000 | | 5y-1= | | 27/20=36/v | | 23w+2=48 | | 10-6d=46 | | 10-6d=4 | | 18=3(-3x-6) | | .025x+x=200 | | (4-3i)+(-5+i)=equation | | x^3+4x^2+2x+6=0 | | 2.5x+x=200 | | (6y+41)+(12y+11)+(9x+1)=180 | | 5y+9=-46 | | v=r | | 2(-14c-7)= | | 8x^2+8=6-9x | | 19/r=152/4 | | x+14=-86 | | 3(n-9)=-21 | | 4x^3+21x^2+28x=-28 | | 45=-4x+1 | | 3q+5=-2q-20 | | 19r=152/4 | | 3q+5=2q-20 | | 4x^2+16=2x^2 | | 7/8=x/28 | | y=lne^2 | | 24+3x=-12 | | 5X-(x+2)=14 | | 7y-5y+3-y=2y-5-3y |